Topics in dynamics of bridges, Volume 3 : proceedings of the 31st IMAC, a conference on structural dynamics, 2013 - Cunha, Alvaro (Conference Proceedings of the Society for Experimental Mechanics Series, 2013)
Topics in Dynamics of Bridges, Volume 3: Proceedings of the 31st IMAC, A Conference and Exposition on Structural Dynamics, 2013, the third volume of seven from the Conference, brings together contributions to this important area of research and engineering. The collection presents early findings and case studies on fundamental and applied aspects of Structural Dynamics, including papers on:   Vibration Monitoring Damping Damage Detection Health Monitoring Dynamic Behavior Dynamic Modeling Human-Induced Vibration